Shear wave elastography in diffuse thyroid disease - Sedlackova, Zuzana; Herman, Jan; Furst, Tomas; Salzman, Richard; Vachutka, Jaromir; Herman, Miroslav (Biomedical papers, 2021)
Aim. Our aim was to examine the contribution of shear wave elastography to ultrasonographic assessment in diffuse thyroid disease, specifically to evaluate the stiffness of the thyroid gland in diffuse thyroid disease and compare it with healthy controls. Methods. A total of 46 patients with diffuse thyroid disease were examined clinically, by conventional ultrasound, and shear wave elastography. The conventional ultrasound parameters followed were: volume, margin quality, presence of nodules, and vascularisation. We measured the mean, minimum, and maximum stiffnesses by shear wave elastography. Results were correlated with values in 128 healthy subjects. Results. Patients with diffuse thyroid disease had significantly higher mean and maximal stiffnesses of the thyroid gland: 12.5 ± 5 kPa and 35.3 ± 12.8 kPa, respectively, and lower minimal stiffness: 0.5 ± 0.6 kPa than the healthy control group with mean, maximal, and minimal values of 9.5 ± 3.6 kPa, 22.5 ± 7.3 kPa, and 2.2 ± 2.1 kPa (P<0.001). Stiffness values were positively correlated with BMI and volume of the thyroid; they did not correlate with margin quality, presence of nodules nor vascularisation. Compared with healthy volunteers, thyroid glands of patients with diffuse thyroid disease had a blurred margin more frequently and the amount of nodules and vascularisation were higher. Patients with Graves-Basedow disease did not have significantly different mean, maximal, nor minimal stiffnesses than those with thyroiditis. Conclusion. Both mean and maximal stiffness of the thyroid gland are significantly higher in diffuse thyroid disease than in the healthy population, while minimal stiffness is lower.
Keywords: diffuse thyroid disease; elastography; shear wave; ultrasound